Niccolò Paganini: the hands of a genius - Pedrazzini, Alessio; Martelli, Alessandra; Tocco, Silvio (Acta Biomedica Atenei Parmensis, 2015)
Niccolò Paganini was a man stricken by many diseases and according to Myron Schonenfield and Renzo Mantero, he may have also suffered from Marfan Syndrome. The following paper is based on actual physical examinations reports made by his contemporary physicians, documented in personal letters In addition, the current investigation presents a comparison between a post-mortem mold of Paganini’s right hand and several paintings of the Maestro drawn by Lyser, his personal portraitist, and the images of the hand of a well-known musician affected by Marfan Syndrome which was treated by the authors. (www.actabiomedica.it)